Collagenous Gastritis in Primary Selective IgM Deficiency: Transition to EBV+ Gastric Adenocarcinoma. (26th May 2021) - Narsai, Tejal; Su, Houfen; Braxton, David; Gupta, Sudhir
Abstract : Selective IgM deficiency (SIgMD) and isolated collagenous gastritis are two independent rare disorders. Our purpose is to report the 1 st case of SIgMD and isolated collagenous gastritis and collagenous gastritis that has transitioned to EBV + gastric adenocarcinoma. Gastric biopsy tissue was analyzed by EBV-related encoded RNA in situ hybridization assay. Subsets of CD4, CD8, T follicular helper cells (TFH ), and members of the "regulatory lymphocytes club" were measured with multiple panels of monoclonal antibodies and isotype controls by multicolor flow cytometry. The patient was diagnosed with SIgMD (extremely low serum IgM 9 mg/dl and normal IgG and IgA and exclusion of secondary causes of low IgM). Soon after SIgMD diagnosis, the patient developed collagenous gastritis and, 8 years later, developed gastric adenocarcinoma that was positive for EBV. An extensive immunological analysis revealed reduced naïve CD4 and CD8 effector memory T cells and increased naïve and central memory CD8 T cells. Among the circulating follicular helper T cells (cTFH ), TFH 1 and TFH 2 were increased whereas TFH 17 was decreased. CD4 Treg cells and TFR cells were increased, whereas Breg and CD8 Treg were comparable to control. In conclusion, SIgMD may be associated with isolated collagenous gastritis, and collagenous gastritis may transition to EBV + gastric adenocarcinoma. A role of regulatory lymphocytes in gastric cancer is discussed.